Searching for new community engagement approaches in the Netherlands: a realist qualitative study - E. De Weger; N. J. E. Van Vooren; H. W. Drewes; K. G. Luijkx; C. A. Baan (BMC, 2020)
Abstract Background Community engagement is increasingly seen as key to improving healthcare systems and to increasing communities' involvement in the shaping of their own communities. This paper describes how 'community engagement' (CE) is understood and being operationalised in the Dutch healthcare system by investigating the CE approaches being implemented in six different regions and by examining engaged citizens' and professionals' experiences of those CE approaches. Methods For this realist study, interviews and focus groups were held with citizens (16) and professionals (42) involved in CE approaches in the six regions. Additionally, CE-related activities were observed to supplement interview data. Results This study shows that citizens and professionals defined and experienced CE differently and that they differed in who they felt had ownership of CE. The CE approaches implemented in community-led initiatives and organisationally-led initiatives varied accordingly. Furthermore, both citizens and professionals were searching for meaningful ways for citizens to have more control over healthcare in their own communities. Conclusion CE can be improved by, first of all, developing a shared and overarching vision of what CE should look like, establishing clear roles and remits for organisations and communities, and taking active measures to ensure CE is more inclusive and representative of harder-to-reach groups. At the same time, to help ensure such shared visions do not further entrench power imbalances between citizens and professionals, professionals require training in successful CE approaches.